Targeted treatment of HPV16-positive and -negative SCC cells with small molecule tyrosine kinase inhibitors and everolimus affects MMP2 and MMP14 expression - Huber, Lena; Birk, Richard; Knüttel, Manuel Thomas; Rotter, Nicole; Aderhold, Marc Christoph; Scherl, Claudia; Lammert, Anne; Jungbauer, Frederic; Kramer, Benedikt (Anticancer research, 2022)
Background/Aim: The rise of targeted therapies in the treatment of head and neck squamous cell carcinoma (HNSCC) has considerably widened the treatment range. Matrix metalloproteinases (MMPs) are key regulators of the tumor development of many cancer entities, which makes them a promising target for new treatment options. We examined the expression patterns of MMP2 and MMP14 in human papillomavirus (HPV)-positive and -negative SCC lines after treatment with small molecule tyrosine kinase inhibitors (TKIs) and a mechanistic target of rapamycin (mTOR) inhibitor in vitro. Materials and Methods: Cells of two human HPV-negative cell lines (UMSCC-11A/-14C) and one HPV-positive cell line (CERV196) were incubated with 20 μmol/l of erlotinib, gefitinib, nilotinib, dasatinib, or everolimus for 24-96 h. Cell proliferation was assessed by proliferation assay and the protein concentrations of MMP2 and MMP14 by sandwich enzyme-linked immunosorbent assay. For statistical analysis, the results were compared with those of untreated SCC cells. Results: MMP2 and MMP14 were expressed in all three tested cell lines; expression levels were highest in the UMSCC-14C cell line. The tested TKIs significantly (p<0.05) reduced MMP2 expression in the UMSCC-14C cell line. In the HPV-positive cell line, the drugs led to an increase in MMP2 and MMP14 expression. Conclusion: Dysregulations in MMP signaling are involved in tumorigenesis and metastasis of HNSCCs; MMP2 has been noted as a potential biomarker. The expression of MMP2 and MMP14 is influenced effectively by small molecule TKIs and everolimus. Based on our data, future research should concentrate on a better understanding of the interplay between tumor microenvironment and tumor cells in vitro and in vivo.